Coccinella repanda Thunberg (Celeoptera: Coccinellidae) Aphidophagus Potensial pada Tanaman Cabai: Biologi, Demografi, dan Tanggap Fungsional Pada Beberapa Kutudaun - Efendi, Siska (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2023)
Coccinella repanda Thunberg (Coleoptera: Coccinellidae) is one of the important predators in pest control of chili plants. However, information about this predator's biology, demography, and functional response is still limited in Indonesia. This study aimed to evaluate the potential of C. repanda by studying its biology, demography, and functional response to several species of main pest aphids on chili plants. Observations of biology and demography were conducted using five replications, with each replication treated with a pair of C. repanda. Observations of preference and predation ability of C. repanda on different prey were conducted using a factorial design with two factors and five replications. The first factor was prey exposure to different densities, and the second was the use of different prey species. Data were analyzed using variance analysis and continued with Duncan's New Multiple Range Tests (DNMRT) at the 5% level. The pre-adult and adult development periods, as well as the longevity of Coccinella transversalis (Thunberg) (Coleoptera: Coccinellidae), were studied in the laboratory using Aphis gossypii (Glover) (Homoptera: Aphididae) as prey. The results showed that the development period of C. repanda was 31.02 Â± 4.73 days. During their lifespan, female adults were able to lay 90.44 Â± 14.38 eggs. The demographic parameters of C. repanda were gross reproductive rate (GRR) of 74.80 individuals per generation; net reproductive rate (Ro) of 18.22 individuals per female per generation; intrinsic rate of increase (rm) of 0.46 individuals per female per day; mean generation time (T) of 12.40 days; and doubling time (DT) of the population for 1.51 days. There was no significant difference in the predation rate of C. repanda on three different prey exposed. Logistic regression analysis also revealed that C. repanda exhibited type I functional response to A. gossypii, A. craccivora, and M. persicae. These results indicate that C. repanda can be categorized as an effective biological control agent. This study is expected to contribute to developing biological pest control strategies on chili plants.